Эколого-морфологическая характеристика Microtus socialis центральной части южного склона Большого Кавказа Азербайджана - Шамилов, Э.Н.; Абдуллаев, А.С.; Кулиев, Г.Н.; Мамедрзаева, Е.Т.; Керимова, З.М.; Азизов, И.В.; Мамeдов, Г.М.; Мурадов, П.З. (Фактори експериментальної еволюції організмів, 2016)
Aim. The objective of this study is to examine the features of the population structure of social voles in Khachmaz
array lowland and highland conditions of Shamakhi region within the Republic of Azerbaijan. Methods. For catching
animals used the «Heroes» type traps. Age groups were determined by generally accepted method, and morphological
parameters of cranial techniques proposed by Schwartz. Results. Populations have similar organization and high stability.
In Khachmaz population social vole sex ratio has clear seasonal differences, while Shamakhi population is homogeneous,
except for the autumn period, when the predominance of females is observed.
Keywords: social voles, burrow, reproduction, embryo, population, female, dimorphism.